Ecotoxicologia do mercúrio (Hg) Podocnemis expansa (Schweigger, 1812) (Testudines, Podocnemididae) do Tabuleiro de Monte Cristo no rio Tapajós, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2012)
The Tapajós basin harbors the largest concentration of Amazon turtle (Podocnemis expansa) nests. There is mercury in the atmosphere, soils and waters in elementary organic and inorganic forms. Methyl mercury is the most toxic form to aquatic organisms, including chelonians, and toxicity is favoured by bioaccumulation and biomagnification. With the aim of analyzing the ecotoxicology of mercury in Podocnemis expansa in the turtle nests of Monte Cristo, we collected 40 adult animals, 66 half-grown turtles and 99 eggs in three segments of the nesting beach established according to the distance of the river canal; segment is 1 nearer to the river and segment 3 more distant from it, with segment 2 of intermediate location between 1 and 3. We registered the parameters of depth, number of eggs, temperature, pH and humidity of the turtle nests. We used non-invasive methods in order to preserve the animals. For the analysis of tissues, muscles, nails, bony shields, egg shells, yolk and whites of the eggs, we used atomic fluorescence spectrometry by cold vapour (CVAFS). We analyzed correlations between concentration of total mercury in corporal tissues and eggs among themselves and with morphometric variables by using the Pearson correlation matrix. We used analysis of variation to test the difference between the levels of total mercury found in adults, half-grown specimens, and eggs, and Tukey´s test to separate significant differences. We interpreted the influence of environmental parameters on concentration of mercury through simple linear regression. We inferred that young animals are entering the reproductive process by using the average data of animals caught, which were 27 kg, 65 cm of bony shield and 87 eggs per turtle nest. The medium concentration found in the tissues of adult females are the following: muscle 55 ng.g -1, bony shield 81 ng.g -1, nails 119 ng.g -1; in eggs: egg-shield 34 ng.g -1, yolk 33 ng.g -1, white 31 ng.g -1, and in the bony shield of half-grown turtles 79 ng.g -1. We found positive correlations between the weight of females and concentration of Hg in the yolk of eggs; between the depth of turtle nests and number of eggs, and Hg concentration in the whites of eggs. Only the concentration in the nails of female adults was significantly different from the concentration in the eggs components. The concentration in the tissues was similar to that in the eggs. We observed significant differences between the muscular concentration of animals caught in segments 1 and 3 as well as in the organic components of eggs in these sections. We concluded that eggs are good indicators of muscular concentration of adults turtles and that Hg disturbs the behavior of animals, keeping them away from the river-bank, a fact that contributes to the loss of turtle nests by the action of river floods, and compromises hatching success with a reduction in the recruitment of animals each breeding season when there are unforeseen increases in the dimensions of the river.
Keywords: Podocnemis expansa; Ecotoxicologia; Mercúrio; Quelônios; Bioacumulação; CNPQ::CIÊNCIAS EXATAS E DA TERRA; ESTUDOS E MANEJOS DOS ECOSSISTEMAS AMAZÔNICOS